Komunitas Mikrofungi pada Lapisan Horizon Serasah Acacia mangium - Samingan Samingan; Lisdar I. Sudirman; Dede Setiadi; Alex Hartana; Budi Tjahjono (Jurnal Agrista, 2008)
Microfungal Community on Litter Horizon Layer of Acacia mangiumABSTRACT. Fungal diversity on litter horizon layer of Acacia mangium were investigated to examined fungal species and fungal community on each litter horizon layer, and also to examined relationship between organic content of litter and fungal community. Twenty two species were isolated from three litter horizon layer with dilution method. Total fungal population on five years old A. mangium standing was higher than two years old, whereas on logging former area was low. Total fungal population on standing two and five years old were highest on L layer follow by F and H layer, but on logging former area were highest F layer followed by L and H layer. Aspergillus was dominate on H layer in almost of sampling collection area, beside that Aspergillus and Penicillium were found also on L and F layer. Generally L and F layer dominated by Sp7, Sp5, Sp20, and Sp22. The highest diversity indice on two years old standing was found at different layer.; L and H on health and Genoderma attacked standing, whereas on standing five years old, highest diversity indices was found at L layer, but on logging former area highest diversity indices was found at H layer.